2014
DOI: 10.1200/jco.2014.32.30_suppl.294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hispanic and non-Hispanic patients with HCC.

Abstract: 294 Background: In the U.S., Hispanics have a higher incidence of hepatocellular cancer (HCC) and higher disease-specific mortality. The country of origin for Hispanics varies throughout the U.S. However, little is known about Hispanics with HCC in the Northeast. We compared Hispanic and non-Hispanic patients with HCC at a Boston teaching hospital. Methods: Hispanic patients with HCC seen at Beth Israel Deaconess Medical Center (BIDMC) from 1998-2012 were identified in our database. Ethnicity was determined f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…26 Babalola, et al confirmed that Latino patients had higher rates of metabolic syndrome, but unlike our study, showed that they also had higher rates of hepatitis C and were more likely to be female than their non-Latino cohort. 27 These differences may have been due to the fact that their cohort was taken from a teaching hospital in Boston, where the majority of their Latino population is Puerto Rican, whereas in our study the majority of our Latino patients are Mexican. Setiawan's longitudinal study also supported the association between metabolic syndrome and HCC development, showing diabetic Latino patients had a 3.3x higher risk of HCC development as compared to non-diabetic Latinos, with a 2.2x higher risk of HCC in diabetic non-Latinos as compared to non-diabetic counterparts.…”
Section: Discussionmentioning
confidence: 77%
“…26 Babalola, et al confirmed that Latino patients had higher rates of metabolic syndrome, but unlike our study, showed that they also had higher rates of hepatitis C and were more likely to be female than their non-Latino cohort. 27 These differences may have been due to the fact that their cohort was taken from a teaching hospital in Boston, where the majority of their Latino population is Puerto Rican, whereas in our study the majority of our Latino patients are Mexican. Setiawan's longitudinal study also supported the association between metabolic syndrome and HCC development, showing diabetic Latino patients had a 3.3x higher risk of HCC development as compared to non-diabetic Latinos, with a 2.2x higher risk of HCC in diabetic non-Latinos as compared to non-diabetic counterparts.…”
Section: Discussionmentioning
confidence: 77%